The Impact of Islamic Values Implementation on Organizational Commitments to Human Resources Management Practices at University of Muhammadiyah Malang - Malik, N; Budi Cantika Yuli, S; ., Sudarti (KnE Social Sciences, 2019)
This study aimed to discover the impact of Islamic values implementation on organizational commitment to the practice of Human Resource Management (HRM) at University of Muhammadiyah Malang (UMM). Islamic values are established on the principles of Islamic wisdoms, namely the faith, sharia and morality. Organizational commitment as a practice of employee behavior towards the organization comprises loyalty and achievement of the vision, mission, values and organization goals. Organizational commitment includes affective commitment, continuance commitment, and normative commitment. This study employed a qualitative approach and was conducted at University of Muhammadiyah Malang (UMM). The subjects of this study were the employees of UMM. The type of data used were primary and secondary data which were obtained through interviews, observation and documentation. Subsequently, the entire data were analyzed by applying qualitative descriptive technique. The results revealed that the implementation of Islamic values had an impact on the organizational commitment primarily to the practice of Human Resource Management for employees at UMM. HRM practices include the employee recruitment processes which requires prospective employees to have strong and trustworthy personality (Surah An Nahl verse 78; Al Qashash verse 26; Al Anfaal verse 27), the employee selection process that looking for candidates who meet the essential requirements of honest, strong, and knowledgeable (Surah Al Baqarah verses 249-250; Al Anfaal verse 60), employees training and career development (Surah Al Baqarah: 30), performance appraisal (Surah Al Kahf: 87-88), and compensation (Surah Al A’Raaf: 85). Keywords: Islamic Values, HRM Practice, Organizational Commitment